Advanced Biomimetic Nanomaterials for Non-invasive Disease Diagnosis - Feng, Zhiyuan; Fan, Hao; Cheng, Lin; Zhang, Huan; Fan, Hong; Liu, Jia (Frontiers in Materials, 2021)
Abstract The physical and mental burden of diseases such as cancers, tumors, cardiovascular diseases and others, required advanced materials and methods for non-invasive disease marker detection, large-scale screening and diagnosis. Biomimetic medical materials are synthetic materials designed to be biocompatible or biodegradable, then developed for use in the medical industry. In recent years, with the development of technology, a variety of biomimetic medical materials with advanced properties have been introduced. Great efforts have been made in the progress of biomimetic medical materials in tissue engineering, regenerative medicine, bioimaging, biosensing and other fields. The latest advance of biomimetic medical materials in disease diagnosis has attracted tremendous interest. Therefore, this review summarizes particularly focuses on the potential of biomimetic nanomaterials in non-invasive disease marker detection and disease diagnosis. The first part focuses on the structure and mechanism of different kinds of advanced biomimetic nanomaterials in disease non-invasive diagnosis. The second part reviews the recent cutting-edge method for non-invasive disease diagnosis using biomimetic nanomaterials. In addition, the existing problems and future development of biomimetic nanomaterials is also briefly described in the third part. The application of biomimetic nanomaterials would provide novel and promising diagnostic method for non-invasive disease marker detection, large-scale clinical screening and diagnosis, promoting the exploitation of devices with better detection performance and the development global clinical public health. Highlight Emerging nanoscience and nanotechnology enable material scientists to design and manufacture biomimetic nanomaterials, which will show great advantages in early non-invasive detection and non-invasive diagnosis of diseases. The novel biosensor and bioimaging based on biomimetic nanomaterials have attractive characteristics and has guiding significance for the development of the application of biomimetic materials. We believe that researchers can design more complex methods and structures based on biomimetic nanomaterials to produce devices with higher detection sensitivity and stability or improve the accuracy of existing imaging methods.